2014
DOI: 10.1016/j.pnsc.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Study on vertical mandibular distraction osteogenesis using magnesium alloy on canine

Abstract: The bone formation feasibility by a novel magnesium alloy device was evaluated using a canine vertical mandibular distraction osteogenesis (DO) model. Osteotomies were performed in the area where last 3 star's teeth of left mandibular were pulled out before 3 months. Both AZ31 magnesium alloy (n¼ 6) and 316L stainless steel (n ¼6) distraction devices were implanted. The distraction osteogenesis was carried out with a latency of 5 days after mandibular osteotomy. Distraction proceeded at a rate of 0.3 mm/8 h fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The biometals Mg, Zn, Cu, Mn, and Co have all been shown to have beneficial effects in bone regeneration. Among the above biometals, Mg and its alloys have been intensively investigated in recent years as a new class of biodegradable materials due to their suitable mechanical properties and low mass density, as well as angiogenic and osteogenic properties [ [71] , [72] , [73] , [74] , 92 , 93 ]. Therefore, we discuss the advantages and disadvantages of Mg in bone regeneration and the potential of using biodegradable Mg to shorten the treatment duration of DO.…”
Section: Overview Of Biometals In Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The biometals Mg, Zn, Cu, Mn, and Co have all been shown to have beneficial effects in bone regeneration. Among the above biometals, Mg and its alloys have been intensively investigated in recent years as a new class of biodegradable materials due to their suitable mechanical properties and low mass density, as well as angiogenic and osteogenic properties [ [71] , [72] , [73] , [74] , 92 , 93 ]. Therefore, we discuss the advantages and disadvantages of Mg in bone regeneration and the potential of using biodegradable Mg to shorten the treatment duration of DO.…”
Section: Overview Of Biometals In Bone Regenerationmentioning
confidence: 99%
“…The degradation characteristic of Mg in the biological environment may also avoid a second surgery for implant removal [ 111 ]. Additional advantages include the low density of the biodegradable Mg alloy and the observation that its degradation products (Mg ions, hydrogen and elevated local pH value) increased expression of multiple endogenous biological agents continuously, resolving the problem of inefficient delivery methods for growth factor therapy, therefore making it a good candidate for accelerating DO [ 93 , 117 ].…”
Section: Advantages and Disadvantages Of Mg In Bone Regenerationmentioning
confidence: 99%
“…The results concluded that bone regeneration and reduction in degradation was enhanced by biodegradable Mg-3.1Nd-0.2Zn-0.4Zr alloy matrix and the brushite coating ( Figure 2). In another study, Wang et al [73] used magnesium alloys for the vertical mandibular distraction of canines. AZ31 magnesium alloys and 316L stainless steel distraction devices were implanted in the canine mandible, and distraction osteogenesis was done at a rate of 0.3 mm/8 h for 7 days followed by 4 weeks of consolidation.…”
Section: Magnesium/magnesium Alloys In Mandibular Reconstructionmentioning
confidence: 99%
“…Furthermore, if the pH around magnesium ionmodified titanium was decreased by inflammation in vivo 32,33) , the sustained release of magnesium ions occurs and can be expected to lead to activation of osteoblasts leading 9) to a reduction in bone resorption 10,11) .…”
Section: Sustained Release Of Magnesium Ionsmentioning
confidence: 99%
“…Moreover, a higher intake of magnesium has been proved to efficiently prevent reduction of bone mineral density (BMD) in patients with osteoporosis 8) . Additionally, some reports suggest that magnesium ions promote bone formation through the activation of osteoblasts 9) and increase in bone morphogenetic protein (BMP-2) 10) . Another report indicates that magnesium implants show properties of less inflammatory response and fibrosis than conventional implant materials 11) .…”
Section: Introductionmentioning
confidence: 99%